Early Miocene Populus L. Fossils Reveal the Northwestward Expansion of the East Asian Summer Monsoon Into Eastern Qaidam - Zhen‐Dong Cao; San‐Ping Xie; Jing‐Nan Huang; Yun‐Zhe Zhang; Zi‐Yi Li; Si‐Hang Zhang; De‐Fei Yan (Journal of Biogeography, 2026)
Aim The evolution of the East Asian Summer Monsoon (EASM) is critical for understanding Asian biodiversity and ecosystem stability. While models and geological records suggest the EASM reached the Qaidam Basin during the Miocene, macrofossil evidence remains scarce. We aimed to test the hypothesis of a northwestward monsoon expansion using newly discovered Populus fossils as bioclimatic indicators. Location Wulan Basin, northeastern Tibetan Plateau, Qinghai Province, China. Taxon Angiosperms (Salicaceae: Populus L.). Methods We conducted morphological analyses on leaf fossils and identified their Nearest Living Relative (NLR). By establishing correlations between the leaf traits of the NLR and modern climatic factors, we reconstructed the paleoclimate of the Wulan Basin. Furthermore, we employed Species Distribution Modelling (MaxEnt) to simulate the potential range of this lineage under Early Miocene conditions to explore monsoon‐driven habitat shifts. Results The late Early Miocene fossils from the Wulan Basin are morphologically most similar to the extant Populus davidiana , a species characteristic of temperate, semi‐humid environments. The presence of this lineage indicates that the Wulan Basin—currently an arid region—experienced significantly higher precipitation and a temperate semi‐humid climate during the Early Miocene. MaxEnt modelling reveals that the suitable bioclimatic envelope for this Populus group extended much further northwest than its modern range, providing a potential biological signal of enhanced moisture transport into the interior of East Asia. Main Conclusions The occurrence of Populus fossils in the Wulan Basin provides a preliminary biological indicator for the northwestward expansion of the EASM into the northeastern Tibetan Plateau during the late Early Miocene, although corroboration from additional proxy records and localities is still needed. This climatic shift, likely driven by the phased uplift of the Tibetan Plateau, transformed the regional hydrological cycle and facilitated the migration of mesic woody taxa into Asia's interior. Our findings highlight the profound impact of tectonic‐monsoon interactions on historical plant distributions.